The Creative Exploitation of Pecha Kucha’s Presentation Technique in English Teaching Classes - Muhajir Muhajir; Awaluddin Syamsu Awaluddin Syamsu (Qalam : Jurnal Ilmu Kependidikan, 2022)
Pecha Kucha has been gaining more acknowledgment in many subjects since the first time it was introduced in 2003 in the architect’s meeting. Currently it has been increasingly utilized in English teaching. Due to its nature as a presentation technique, it has been incorporated in English speaking   classes. Furthermore, it was also employed in reading, writing, and translation classes. This paper   aimed at reviewing research articles of the incorporation of Pecha Kucha in English classes in higher education. After the review, the formulation of the Pecha Kucha use for teaching English will be presented. The result indicated that Pecha Kucha can be incorporated in English classes with various ways such as employing it as formative and summative assignments in personal or group based works. It can be also used in person or online classroom teaching settings. Furthermore, the strict rules of Pecha Kucha can be adjusted according the needs of the teaching context so this presentation technique offers new and promising technique. Keywords: Pecha Kucha, English teaching, teaching method, ESL, EFL